Gender, HIV/AIDS & status of teachers : report - Degazon Johnson, Poli (Commonwealth Secretariat LondonGB, 2008)
Looks at teacher mobility, gender and status. Focuses on the impact of HIV/AIDS on education and the teaching profession.